Scientific and pedagogical staff as a social community in the changing conditions of academic development - G. E. Zborovsky; P. A. Ambarova (Russian State Vocational Pedagogical University, 2022)
Introduction. The urgency of the problem is due to the need to increase the scientific activity and productivity of scientific and pedagogical staff (SPS), acting as the flagship of the scientific development of universities. The article examines the social community of SPS of Russian universities as one of the drivers of the development of Russian higher education in the context of the implementation of the strategic academic leadership programme "Priority-2030".The aim of the article is to identify the directions and contradictions of the transformation of the scientific and pedagogical community in the changing conditions of academic development of Russian universities.Methodology and research methods. The study uses the method of analysing statistical data on higher education in Russia and the Ural Federal District for 2000-2021 and Monitoring the effectiveness of universities for 2013-2021.Results. The main results of the study presented in the article were quantitative, structure and substantive characteristics of the social community of the SPS. They were shown through the prism of indicators of their scientific activity and the requirements imposed on them by the university administration. An important result of the study was the analysis of the achievements and problems of scientific activity of the SPS in five universities of the Ural Federal District, representing five subjects of the Russian Federation on its territory - Sverdlovsk, Chelyabinsk, Tyumen, Kurgan regions, Khanty-Mansi Autonomous District. Among the universities coming into focus, there were three universities, which received support within the framework of the "5-100" Project. The article identifies the prospects and risks of implementing projects for the development of the university SPS in the "core zone", which have received support under the "Priority-2030" strategic academic leadership programme, as well as the opportunities for academic development of the SPS of universities in the "semi-periphery" and "periphery" that do not have such large-scale state assistance.The approaches are proposed to create favourable conditions for the SPS transformation. Taking into account such approaches, it is possible to overcome imitation and a steady increase in SPS scientific activity and productivity. The authors draw attention to the need to differentiate the conditions of professional activity of productive and unproductive SPS, a group of young SPS. The authors argue the importance to use the strategy of "growing" one's own SPS as the basis for the real implementation of the strategic objectives of the "Priority-2030" programme and taking care of the human capital of universities. It is also concluded that the modern social context of Russian higher education limits the possibilities of solving this problem and needs to be changed.Scientific novelty. The novelty of the research consists in a comparative analysis of trends and contradictions in the transformation of the SPS of Russian universities, their scientific potential, areas of activity and social functions in the changing conditions of academic development of universities.The practical significance of the article is to demonstrate the possibilities and results of the transformation of the SPS on the way to their transformation into a driver of scientific development of universities.